2007
DOI: 10.1097/icl.0b013e31803c55ad
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Contact Lens Solutions Using Confocal Laser Scanning Microscopy and the In Vitro Bovine Cornea

Abstract: OPTI-FREE Express has the potential for deeper mitochondrial effects compared to ReNu MultiPlus No Rub and Hanks' balanced salt solution controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…On the other hand, although there is some evidence of cytotoxicity in cell culture studies, in general the response is not accompanied by changes in cell morphology, metabolism or viability, membrane integrity or barrier function or the expression of apoptotic or inflammatory markers (Bantseev et al, 2007) This has suggested that transient hyperfluorescence is not adequately explained by and due to, uptake of fluorescein into damaged epithelial cells.…”
Section: Fluorescein Spread Within the Epitheliummentioning
confidence: 84%
“…On the other hand, although there is some evidence of cytotoxicity in cell culture studies, in general the response is not accompanied by changes in cell morphology, metabolism or viability, membrane integrity or barrier function or the expression of apoptotic or inflammatory markers (Bantseev et al, 2007) This has suggested that transient hyperfluorescence is not adequately explained by and due to, uptake of fluorescein into damaged epithelial cells.…”
Section: Fluorescein Spread Within the Epitheliummentioning
confidence: 84%
“…Additionally, most in vitro studies show PHMB‐based solutions have minimal toxicity, including those that used the most sensitive assays . Furthermore, a large proportion of studies has shown PHMB‐based solutions are less cytotoxic than those containing PQ‐1/Aldox, which show a lower intensity of SICS/PATH.…”
Section: Aetiology Of Sics/pathmentioning
confidence: 99%
“…The stained cornea, limbus, and bulbar conjunctiva was placed on a glass container and immobilized with 1% agarose gel previously melted in Hanks balanced salt solution, as described previously. 16 The staining was initiated immediately after dissection, and microscopy was performed within 3 hours after enucleation.…”
Section: Methodsmentioning
confidence: 99%